Penambahan Latihan Core Stability terhadap Performa Ekstremitas Atas pada Atlet Basket - Nadia Nesiya T.B. Pertiwi; Restu Arya Pambudi; Ganesa P.D. Kurniawan (Jurnal Terapi Wicara dan Bahasa, 2026)
Background: Upper extremity performance is an important component in basketball that influences the success of techniques such as passing and shooting. Core muscle stability serves as the linking mechanism for force transfer from proximal to distal segments; insufficient core stability can reduce movement accuracy and arm strength. Objectives: This study aimed to determine the effect of adding core stability exercises on upper extremity performance in basketball athletes. Methods: A quasi-experimental design with a two-group pretest-posttest design was employed. The sample consisted of 28 basketball athletes aged 14–18 years selected by purposive sampling, divided into a treatment group (routine training + core stability, n=14) and a control group (routine training only, n=14). The intervention was conducted for 4 weeks at a frequency of 3 times per week. Upper extremity performance was measured using the Upper Quarter Y-Balance Test (UQYBT). Results: Based on paired Sample T-Test results showed significant improvement in upper extremity performance in both the treatment group (p=0.000) and the control group (p=0.001–0.002). The mean improvement of the treatment group was greater than the control group: 1.21±0.53 (right) and 0.93±0.45 (left) compared to 0.41±0.37 (right) and 0.29±0.29 (left). The Independent T-Test showed a significant difference between the two groups (p=0.000). Conclusion: The addition of core stability training significantly improved upper extremity performance in basketball athletes, with a greater effect compared to routine training alone. Keywords : Upper Extremity Performance, Basketball Athletes, Core Stability Exercise, Upper Quarter Y-Balance Test.